Amazon India's "Apni Dukaan": branding strategy. Issue 3 (20th August 2018) - Yadav, Neetu; Sagar, Mahim
Abstract : Subject area: Brand Management, Branding Strategy, Strategic Management. Study level/applicability: The case study is suitable for postgraduate management programs, such as MBA, Executive MBA and executive development programs. Case overview: This case study provides a detailed analysis of Amazon India's branding strategy by way of analyzing popular branding campaigns such as "Try to kar", "Aur Dikhao", "Kya Pehnu" and "Apni Dukaan" that enabled the global brand to reach to the masses of Tier-II and Tier-III cities in India. Facing fierce competition from existing market leaders such as Flipkart and Snapdeal, Amazon India strategizes to attract Indian consumers by rightly capturing their behavior in terms of demanding "highest power of options", "fashion choices", "originality" and "trust" with its local flavored advertisement campaigns enabling it to create a "trusted, reliable and local" brand identity. With the help of sufficient data and numbers about the industry, company and competitors, the analysis presents a clear picture of the current status of Amazon in the Indian e-commerce space and leaves the readers with food for thought concerning whether this "culture-specific" branding strategy will enable Amazon to become the number one choice for Indian online shoppers in the near future. Expected learning outcomes: This case study helps students to understand how global MNCs use unique branding strategies to capture mass-markets in e-commerce business, the role of culture-specific aspects in developing differentiation strategies and the role of local flavors in branding strategies and internationalization. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 8: Marketing.